Investigating Breakdown Strength Based on Trapping Profile in Cross-Linked Polyethylene (XLPE) Nanocomposites - Muhammad B. MUHAMMAD; Noor S. B. MANSOR; Fariha R. KHAN (FUDMA Journal of Engineering and Technology, 2026)
Mobile charge accumulation can negatively impact the performance of cross-linked polyethylene insulation. This increases the local electric field within the insulation material, reducing the probability of breakdown. The introduction of zinc oxide (ZnO) nanofillers in insulation materials is expected to reduce the mobility of charge carriers. Therefore, the objective of this research work is to investigate the effect of ZnO nanofillers on the breakdown strength of Cross-Linked Polyethylene, based on trapping profiles. The effect of ZnO nanofillers at concentrations of 0.5 wt%, 1.0 wt%, and 1.5 wt% was evaluated by photoluminescence, with the selected range corresponding to low filler loadings that promote uniform dispersion and suppress nanoparticle agglomeration. The result from the photoluminescence test provides two distinct peaks at different energy level, the lower energy level indicates shallow traps that causes premature failure in insulation owning to the ease with which it releases charge carriers back to conduction band promoting formation of conduction pathways, while the higher energy level indicates deep traps that requires greater energy to release the captured charge carriers back to the conduction band which prolong the detention of the charge carriers and in turn retard the formation of conduction pathways. The density of shallow traps decreases with increasing concentration of zinc oxide (ZnO); conversely, the density of the deep traps increases with increasing concentration of zinc oxide (ZnO). As a result, the alternating current (AC) breakdown field strength and reliability of cross-linked polyethylene (XLPE) were improved, as supported by the alternating current (AC) breakdown strength test.